Characteristic of thermal energy system self-driven by exhausted heat from equipment in lunar base. (August 2022) - Zhang, Kai; Sun, Peijie; Li, Shuangfei; Spataru, Catalina; Lv, Xiaojing; Weng, Yiwu
Highlights: A novel self-driven TES used exhausted heat without extra power is proposed. The mathematical model of the TES is established. Off-design performances with fluctuation of Te, Tre and Tc are analyzed. Characteristic of typical conditions considering astronauts' schedule are obtained. The TES provides huge potential capacity on energy saving and weight reducing. Abstract: Considering the challenges of the huge temperature difference of lunar surface between day and night and the shortage of energy in Lunar Base at nighttime mode, this paper proposed a novel topology of self-driven thermal energy system (TES), combined with the power cycle and the ejector refrigeration cycle. The mathematical model of the TES is constructed to obtain the thermal performance under the design condition. Various characteristics of Te, Tre and Tc are studied due to the diversity and fluctuation of exhausted heat grade from equipment in the lunar base. Four typical conditions considering the requirements of heat dissipation and cooling capacity are analyzed when astronauts' schedule and external solar radiation intensity are changed. Results show that the TES realizes self-driven operation without extra power under the design condition and provide 10.26 kW cooling capacity for manned module. Under off-design conditions, evaporation temperature has a significant impact on the refrigeration performance of the TES. When evaporation temperature rises from 312.15 K to 318.15 K, cooling capacity increases from 2.99 kW to 16.02 kW and COP increases from 0.10 to 0.53. When astronauts' schedule changes from sleeping to working at nighttime mode, cooling capacity rises from 3.78 kW to 11.53 kW, meeting the demand for refrigeration. Moreover, the TES has better heat dissipation performance when it is installed in the area above 35 °N. This system with obvious self-driven characteristic will provide huge potential capacity on energy saving and weight reducing, which supplies novel insights on the technical operation of Lunar Base in the future.